Immune priming in the insect gut: a dynamic response revealed by ultrastructural and transcriptomic changes - Moritz Baur; Nora K. E. Schulz; Lilo Greune; Zoe M. Länger; Jürgen Eirich; Iris Finkemeier; Robert Peuß; Petra Dersch; Joachim Kurtz (BMC Biology)
Abstract Background Research on forms of memory in innate immune systems has recently gained momentum with the study of trained immunity in vertebrates and immune priming in invertebrates. Immune priming is an evolutionary ancient process that confers protection against previously encountered pathogens. However, despite the existence of immune priming across many invertebrate taxa, evolution and mechanisms of immune priming are still not well understood. Moreover, it is unclear how natural pathogens might elicit immune priming in their hosts. Results Here we combine RNA sequencing with transmission electron microscopy to investigate the dynamic processes during priming in the gut of a well-established model for oral immune priming, consisting of the host Tribolium castaneum and its natural pathogen Bacillus thuringiensis tenebrionis (Btt). We show that priming with specific, pathogen-derived virulence-relevant factors induces gut damage in T. castaneum larvae, triggering an early physiological stress response and upregulation of a distinct set of immune genes. This response diminishes over time yet enables the gut to upregulate genes known to interfere with Btt virulence when later exposed to infectious Btt spores. Conclusions Our findings demonstrate that pathogen-derived factors inducing gut damage and stress responses prime gut tissue to provide more efficient protection against infection. These insights deepen our understanding of the mechanisms driving innate immune memory, which likely evolved as an adaptive response to natural pathogens.